Olaparib maintenance therapy in patients with platinum‐sensitive, relapsed serous ovarian cancer and a BRCA mutation: Overall survival adjusted for postprogression poly(adenosine diphosphate ribose) polymerase inhibitor therapy. Issue 12 (8th April 2016) - Matulonis, Ursula A.; Harter, Philipp; Gourley, Charlie; Friedlander, Michael; Vergote, Ignace; Rustin, Gordon; Scott, Clare; Meier, Werner; Shapira‐Frommer, Ronnie; Safra, Tamar; Matei, Daniela; Fielding, Anitra; et al.
Abstract : BACKGROUND: Maintenance treatment with the oral poly(adenosine diphosphate ribose) polymerase (PARP) inhibitor olaparib (Lynparza) in Study 19 (study number, D0810C00019; ClinicalTrials.gov identifier, NCT00753545) significantly improved progression‐free survival in comparison with a placebo for patients with platinum‐sensitive, relapsed serous ovarian cancer with a BRCA1/2 mutation ( BRCA m), but an interim analysis revealed no statistically significant overall survival (OS) benefit. However, 23% of the patients receiving the placebo switched to a PARP inhibitor after progression. To investigate whether this had a confounding effect on OS, this article reports an exploratory post hoc analysis that excluded all patients from sites where 1 or more placebo patients received postprogression PARP inhibitor treatment. METHODS: In Study 19, 136 of the 265 patients receiving olaparib or a placebo had a BRCA m. Sixteen patients treated at 11 of the 82 investigational sites received a PARP inhibitor after progression; these sites were excluded from this analysis, and 97 BRCA m patients at 50 sites were included. OS was assessed with a Cox proportional hazards model analogous to the primary study analysis. A supporting rank‐preserving structural failure time (RPSFT) model analysis was undertaken for all 136 BRCA m patients. RESULTS: The OS hazard ratio (HR) was 0.52 (95% confidence interval [CI], 0.28‐0.97) for the 97 BRCA m patients, whereas for the interim OS analysis with all 136 BRCA m patients, it was 0.73 (95% CI, 0.45‐1.17). The supportive RPSFT analysis HR was approximately 0.66. CONCLUSIONS: The numerical improvement in the OS HR suggests that in Study 19, postprogression PARP inhibitor treatment had a confounding influence on the interim OS analysis for BRCA m patients. There is a degree of uncertainty due to the small sample size and the lack of data maturity. Cancer 2016;122:1844–52 . © 2016 American Cancer Society . Abstract : Maintenance therapy with olaparib, a poly(adenosine diphosphate ribose) polymerase inhibitor, in patients with platinum‐sensitive, relapsed serous ovarian cancer and a BRCA mutation significantly improves progression‐free survival in comparison with a placebo, according to an interim analysis. However, BRCA mutation carriers receiving a placebo who switch to a poly(adenosine diphosphate ribose) polymerase inhibitor after disease progression are suggested by a post hoc analysis to have a confounding influence on the interim overall survival analysis.